Directory of trade information services and products in the Caribbean Community (The Agency Christ ChurchBB, 1996)
Provides detailed descriptions of the trade information services and products for ninety organisations in thirteen CARIFORUM Member States. Supplies also a brief description of one hundred and thirty computerised databases maintained by the organisations listed.
Keywords: DIRECTORIES